PENGARUH POSISI KERJA ERGONOMI TERHADAP LOW BACK PAIN (LBP) PADA PEKERJA BATIK DI KAUMAN SOKARAJA - Harwanti, Siti; Aji, Budi; Ulfah, Nur (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2016)
Sitting position on the batik worker in the long term and do repeatedly with high accuracy, the position of having the risk of LBP. Based on survey 52 workers (86.7%) experienced LBP. This research used Quasi Esperimental with working position ergonomic. Sample used in this study were 15 workers. The analysis data used non-parametric Wilcoxon test. Results showed no effect of working position ergonomics to LBP before and after using the model position ergonomic work on the first day with a value of p = 0.001, no effect of working position ergonomics of the complaint LBP before and after using the working position ergonomics good day 2 with a value p = 0.000, no effect of ergonomic working position against LBP complaints before and after using the ergonomic working position either day 3 with p = 0.000.